Добро пожаловать в ад: [роман] / Андрей Дышев - Дышев Андрей Михайлович (Черная кошка, 2003)
Экземпляры: (20200210) / Инвентарный номер: 29097 / Цена: 58.00 / Сис.шифр: Р2 / Авт.знак: Д 91 / ГРНТИ: 17 / ББК: 84(2Рос=Рус)6